The Communal Democracy of Yogyakarta Special Region’s Government on the Islamic Law Eclecticism Perspective - Hariyanto; Hanif Fudin; Muhammad Fauzan; Kadar Pamuji; Tedi Sudrajat (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
Law Number 13 of the Year 2012 on Yogyakarta Special Region’s privileges containing a legal affirmative democracy system leads to the weakening of democracy and has implications for non-substantive democracy. It furthermore reflects the normative ambiguity of the democratic system which legitimizes Yogyakarta’s privileged affairs. Therefore, this research aims to analyze Yogyakarta’s privileged affairs based on Islamic Law Eclecticism by reconstructing the democratic system in Law Number 13. Using the normative-doctrinal method accompanied by statutory and conceptual approaches, this research used the content analysis method and legal descriptive techniques. This research shows that the democratic system of DIY is crystallized and simultaneously presented in the form of the Trilogy of Yogyakarta Democratic Principles. Those consist of ngencengke oyot, ngencengke pang, and njagani godhong lan kembang. Based on this, the reconstruction of the democratic system of Yogyakarta’s privilege affairs leads to communal democracy as a form of revitalizing its privilege affairs. Besides, that trilogy, based on Islamic Law Eclecticisms, refers to the interconnection of maqâṣid al-syarī’ah cum-rechtsidee and al-‘urf. The reconstruction of the democratic system in Law Number 13 potentially revitalizes Yogyakarta’s privileged affairs by making local wisdom its core value.